Area-selective growth for patterning and separation of molecules at allocated sites: Designed kinetic Monte Carlo simulation for anisotropic molecules - Yue Jiang; Liang Shi; Naibo Chen; Laigui Hu; Wenchong Wang; Qingmiao Nie; Bo Yan (Results in Physics, 2023)
Micro-patterning of organic thin films plays a crucial role for organic electronics. Due to the high resolution over large areas, several photo-lithography compatible techniques for the patterning of organic films were developed. As a promising candidate, area-selective growth (ASG), i.e., the growth of molecules on patterned surface for nucleation control, has been proposed. Experimentally, two typical molecules, categorized into non-planar and planar molecular configuration, exhibit different growth behavior, which is mechanistically attributed to binding energy difference and step-edge induction on patterned surface. Benefiting from the diffusion and nucleation sites control of the different configuration molecules, patterning and separation of multi-species molecules at micro-scale were demonstrated. For the ASG of non-planar molecules, the molecular dynamics has been well explored using the kinetic Monte Carlo (KMC) simulations. However, little attention is paid to the step-edge induced ASG for anisotropic molecules. Here, we introduce a coarse-grained anisotropic interaction model in the KMC algorithm to simulate the step-edge induced ASG. Our results reveal that the edges of electrode (Au) patterns become preferential nucleation sites at initial stage, followed by the lateral growth of subsequent particles due to the strong π-π interactions. In combination with the KMC simulation for binding energy difference mechanism, separation of different particles on designed locations are theoretically demonstrated to mimic the molecular separation that experimentally observed. Our results also validate the KMC simulation as a powerful means for the ASG process of anisotropic molecules in a microscopic view, in addition to the ASG process of isotropic molecules. We believe that the KMC method will provide a deeper insight of the ASG method for organic molecules with different molecular architectures.